2022
DOI: 10.1111/jch.14554
|View full text |Cite
|
Sign up to set email alerts
|

The role of renal nerve stimulation in percutaneous renal denervation for hypertension: A mini‐review

Abstract: Recent trials have demonstrated the efficacy and safety of percutaneous renal sympathetic denervation (RDN) for blood pressure (BP)-lowering in patients with uncontrolled hypertension. Nevertheless, major challenges exist, such as the wide variation of BP-lowering responses following RDN (from strong response to no response) and lack of feasible and reproducible peri-procedural predictors for patient response. Both animal and human studies have demonstrated different patterns of BP responsesfollowing renal ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Renal denervation is used to lower the blood pressure of hypertensive patients via the inhibition of sympathetic activity [99][100][101]. It may have beneficial effects in other indications beyond hypertension, such as renal failure [102,103] and atrial fibrillation [104].…”
Section: Renal Denervation and Atherosclerosismentioning
confidence: 99%
“…Renal denervation is used to lower the blood pressure of hypertensive patients via the inhibition of sympathetic activity [99][100][101]. It may have beneficial effects in other indications beyond hypertension, such as renal failure [102,103] and atrial fibrillation [104].…”
Section: Renal Denervation and Atherosclerosismentioning
confidence: 99%
“…Published guidelines in 2023 [8] recommended the use of opioids and benzodiazepines for the monitored anesthesia care approach. And some studies [9] reported the use of propofol combined with remifentanil to provide sedation and analgesia during RDN. Nevertheless, inappropriate anesthetic regimen can lead to airway and hemodynamic instability and can interference treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…RNS was performed immediately before and after RDN in bilateral proximal (approximately the midpoint of the proximal half of main renal artery) and distal (≈ 1 cm proximal to the bifurcation of branch renal arteries) main renal arteries using the 4 Fr quadripolar catheter (Advanced St. Jude Fix 4 polar Supreme 4F JSN), with bipolar stimulation from poles 1 to 2 (Figure [A]), under general anesthesia by intravenous infusion of a therapeutic dose (0.5–0.7 ml/kg/h) of propofol. 2 The pacing frequency was set at 10 Hz and the pacing output at 20 mA, with a pulse duration of 10 ms. All patients underwent 24-hour ambulatory BP monitoring at baseline and 6 months after RDN. Antihypertensive medications as prescribed at baseline were required to be taken at least 24 hours before ambulatory BP monitoring performed 6 months after RDN to make the results comparable under the same medication burden.…”
mentioning
confidence: 99%